Effect of Automechanic Works on Lead and Iron Content in Two Mechanic Villages in Port Harcourt, Rivers State Nigeria - OS Edori; ES Edori (Journal of Applied Sciences and Environmental Management)
Forty soil samples were collected from two mechanic workshops (villages), Mile 2, Anyama and Mile 3, zone C and a control, UST to examine the pH, conductivity and the concentrations of lead (Pb) and iron (Fe). The pH at the top soil samples (0-15cm) were formed to be higher than those of the lower soil samples (15-30cm). pH values ranged from 7.3- 8.4. The values observed for conductivity also followed the same pattern as the pH with the top soil samples(0-15cm) having higher conductivity values than those of the lower soil samples (15-30cm) and were within the range of 7.70 × 10 - 6.60 × 102 μS/cm. The values of the pH and conductivity were higher in the mechanic workshops than the control. The concentration of Pb were very low at UST(control), which were 4.09mg/kg for the top soil and 3.44mg/kg when compared to those observed at the mechanic workshops which were within the range of 205.50mg/kg 1551.25mg/kg. The value of Pb was highest at Mile 3 zone C 1 (155.25mg/kg) and lowest at Mile 3 zone C 2 (205.50mg/kg). Iron (Fe) concentration was lowest at UST (control), being 1412.50mg/kg (top soil) and 2325.00mg/kg (lower soil) and was highest at the Mile 2, Anyama 1 workshop which was 13162.50mg/kg (top soil) and 13050.10mg/kg (lower soil). The work showed that the contribution of heavy metals into the soil through anthropogenic activities at the workshops is alarming.